Praxis Dialogue: Catholic Rituals in Native American Contexts - Hornborg, Anne-Christine (Peeters Publishers, 2009)
Using rituals as a means of dialogue has been a vital strategy for cross-cultural interchange. Starting with the study of ritual practices, this article discusses the dialectic interface between the Canadian Mi’kmaq Indian traditions and Catholicism, the latter brought into Mi’kmaq territory by French missionaries as early as the beginning of the 17th century. To fully understand the Mi’kmaq relation to Catholicism, four different contexts are considered. The Mi’kmaq have practised Catholicism within a colonial framework, but they have not passively adopted power structures and colonial religion into their communities. Instead, they have interpreted the new conditions by building models both of the world and for the world. In these creative cultural processes, rituals have played a decisive role in moulding a Mi’kmaq way of being in Canadian society.